How a Bacillus “Sees” the World: Information Needs and Signaling Resources of Mycobacterium Tuberculosis - Jorge Navarro; Pedro C. Marijuán (tripleC: Communication, Capitalism & Critique)
Any living cell parasitizing a host organism is immersed into a molecular environment of unfathomable complex- ity. For the advancement of its life cycle in such “hostile” a territory, the cell has to carefully sense its environment, “see” the ongoing physiological processes taking place, and guide subsequently its own network of self-construction processes, pathological responses included. We will discuss how this informational matching occurs in the bacillus Mycobacterium tuberculosis, and how transcriptional programs within the global transcriptional regulatory network are deployed in response to specific signals from the environment and from within the cell itself. In the era of the bioinformatic revolution and of sys- tems biology, it is perhaps surprising that the functional interconnection between the transcription network and the signaling system is far from clarified yet. In the extent to which the living cell can be considered as one of the central paradigms of the nascent information science, this discussion also becomes one about the essential cluster of concepts which should poten- tially apply to the analysis of other information-based entities.